Shank3 regulates striatal synaptic abundance of Cyld, a deubiquitinase specific for Lys63‐linked polyubiquitin chains. Issue 6 (11th July 2019) - Jin, Chunmei; Kim, Shinhyun; Kang, Hyojin; Yun, Ki Na; Lee, Yeunkum; Zhang, Yinhua; Kim, Yoonhee; Kim, Jin Young; Han, Kihoon
Abstract: The SH3 and multiple ankyrin repeat domains 3 (Shank3) proteins are core organizers of the postsynaptic density in neuronal excitatory synapses, and their defects cause various neurodevelopmental and neuropsychiatric disorders. Mechanistically, Shank3 directly and indirectly interacts with hundreds of synaptic proteins with diverse functions and potentially exerts its regulatory roles in synaptic development and function via these interactors. However, Shank3‐dependent regulation of synaptic abundance has been validated in vivo for only a few Shank3 interactors. Here, using a quantitative proteomic analysis, we identified 136 proteins with altered synaptic abundance in the striatum of Shank3 ‐overexpressing transgenic (TG) mice. By comparing these proteins with those found in a previous analysis of the postsynaptic density of Shank3 knock‐out (KO) striatum, we identified and confirmed that cylindromatosis‐associated deubiquitinase (Cyld), a deubiquitinase specific for Lys63‐linked polyubiquitin chains, was up‐ and down‐regulated in Shank3 TG and KO striatal synapses, respectively. Consistently, we found that the synaptic levels of Lys63‐linked polyubiquitin chains were down‐ and up‐regulated in the Shank3 TG and KO striata, respectively. Furthermore, by isolating and analyzing the synaptic Cyld complex, we generated a Cyld interactome consisting of 103 proteins, which may include Cyld substrates. Bioinformatic analyses suggested associations of the Cyld interactome with a few brain disorders and synaptic functions. Taken together, these results suggest that Shank3 regulates the synaptic abundance of Cyld in the mouse striatum and, thereby, potentially modulates the Lys63‐linked polyubiquitination of striatal synaptic proteins. Abstract : The striatum‐enriched Shank3 proteins are core scaffolds in the postsynaptic compartment, and genetic variants of the SHANK3 are causally associated with numerous brain disorders. Here, we show that Shank3 positively regulates striatal synaptic abundance of Cyld, a deubiquitinase specific for Lys63‐linked polyubiquitin chains. Consistently, the synaptic levels of Lys63‐linked polyubiquitin chains were down‐ and up‐regulated in the striatum of Shank3 overexpressing and knock‐out mice, respectively. Therefore, Shank3 dosage affects Lys63‐linked polyubiquitination of the striatal synaptic proteome via Cyld. We think that this can be a novel mechanism by which Shank3 controls striatal synaptic development and function.